Structural and electronic characterisation of π-extended tetrathiafulvalene derivatives as active components in field-effect transistors. Issue 33 (25th July 2016) - Campos, Antonio; Oxtoby, Neil; Galindo, Sergi; Pfattner, Raphael; Veciana, Jaume; Bromley, Stefan T.; Rovira, Concepció; Mas-Torrent, Marta
Abstract : The rigidification of the molecule in π-extended tetrathiafulvalenes is beneficial for reducing the reorganisation energy but has an unfavorable impact on the electronic dimensionality, as observed in the resulting transistors. Abstract : The electronic and structural properties of two tetrathiafulvalene derivatives bearing aromatic benzene rings are reported. Thin film transistors of these materials show p-type characteristics with comparable mobility values. It is found that the rigidification of the molecule is beneficial for reducing the reorganisation energy but also has an unfavorable impact on the electronic structure dimensionality.